Wire rod for high-ductility umbrella rib and production method of wire rod

Through component design and post-rolling online isothermal treatment process, a high-ductility umbrella bone strip mainly based on bainite structure was formed, which solved the problems of insufficient ductility of carbon steel umbrella bone strips and high cost of annealing process in the prior art, and achieved high ductility and low-cost umbrella bone material production.

CN119685697APending Publication Date: 2025-03-25QINGDAO SPECIAL STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598646.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing carbon steel strips for umbrella bones are insufficient in ductility, and are prone to cracking through direct processing. The annealing process is high in cost and energy-consuming, making it difficult to meet the requirements of high ductility performance.

Method used

Through component design and post-rolling online isothermal treatment process, the steel composition is optimized to form strips with mainly bainite structure to improve the plasticity of the steel. Specific steps include iron desulfurization, converter smelting, LF refining, protective casting, rolling and salt bath isothermal treatment.

Benefits of technology

The production of high-ductility umbrella bone strips has been achieved, with a surface shrinkage rate of more than 15% higher than that of traditional umbrella strips. After cold drawing, it can be directly processed into umbrella bone material. The cold processing performance is better than 35 steel, and the surface quality pass rate is ≥99%, which reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685697A_ABST
    Figure CN119685697A_ABST
Patent Text Reader

Abstract

The invention provides a wire rod for a high-ductility umbrella rib and a production method thereof. The wire rod comprises the following main components in percentage by weight: 0.15-0.30% of C, less than or equal to 0.17% of Si, 0.60-1.20% of Mn, less than or equal to 0.025% of P, less than or equal to 0.025% of S, 0.010-0.05% of Ti and 0.0005-0.0040% of B. The production method comprises the steps of molten iron pretreatment, refining, continuous casting, casting blank finishing, heating rolling, online isothermal treatment and the like. Through component design, boron and titanium microalloying grain refinement and online isothermal phase change after rolling, a bainite-based high-plasticity structure is obtained, the tensile strength difference of the same circle of the prepared wire rod is smaller than or equal to 30 MPa, the area reduction rate is 75-85% and is improved by 15% or above compared with traditional steel, and the yield of the prepared wire rod is greatly improved. The requirement that the umbrella rib material is directly machined without annealing after large-deformation continuous cold drawing can be met, the bottleneck problem of the low-carbon production process of the umbrella rib material at present is solved, the machining cost is reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal wire manufacturing, and in particular relates to a wire rod for high-ductility umbrella ribs and a production method thereof. Background Art

[0002] Umbrella rib steel wire rod is the raw material for making high-grade umbrella ribs. The parent material must have high strength and plasticity. At present, the raw material for making U-shaped umbrella ribs in the market is carbon steel wire rod. Since the ribs need to be drawn and flattened to undergo large deformation, the flat wires are prone to cracking during flattening due to their low plasticity. In order to meet the requirement of no cracking ratio ≥ 99%, the fine wires must be annealed before flattening to eliminate drawing work hardening and improve plasticity, thereby solving the problem of flat wire cracking.

[0003] At present, 35 steel is mostly used in the market to make umbrella rib materials. The processing technology is that the hot-rolled wire rod undergoes multiple drawing (reduction of diameter by more than 75%)-annealing-flattening-bending and other processes to obtain U-shaped bent umbrella rib materials. The plasticity of the steel wire is affected by the initial plasticity of the wire rod and the loss of cold working hardening. The plasticity of the material is further lost during the flattening and elongation process, which eventually causes the material to crack. Therefore, an annealing process needs to be added in the middle, but the annealing process is a high-cost, high-energy-consuming, and high-time-consuming process. With the implementation of the "dual carbon" policy and the demand for energy conservation and cost reduction by production units, the development of environmentally friendly and high-ductility steel wire rods for umbrella ribs can save energy and reduce consumption, reduce production costs, and has certain economic value and social significance.

[0004] Since the drawing and flattening processes determine the size of the finished product and cannot be optimized for the time being, the key to developing annealing-free, environmentally friendly, high-ductility steel for umbrella ribs is to improve the plasticity of the wire rod raw material. From the analysis of the material deformation mechanism, refining or controlling a high-plasticity structure is the only way to simultaneously improve strength and plasticity. At present, the 35 steel used for umbrella ribs belongs to medium-carbon carbon steel. According to its phase transformation law, austenite phase transformation occurs when the cooling rate after rolling is greater than 11°C / s to obtain a higher fine pearlite structure. This is difficult to achieve stably under the equipment conditions of the high-speed wire Stelmor air-cooled line, and there is a problem of uneven structure at the overlap points and non-overlap points. Therefore, it is difficult to solve the technical problem of high ductility requirements for umbrella rib steel. Summary of the invention

[0005] Aiming at the technical problems in the prior art that carbon steel wire rods for U-shaped umbrella ribs have insufficient ductility and are prone to cracking when directly processed without annealing, the present invention proposes a process based on component design and online isothermal treatment after rolling to obtain a wire rod with a bainite structure as the main structure, thereby improving the plasticity of the wire rod raw material and obtaining a wire rod for umbrella ribs with high ductility.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A high-ductility wire rod for umbrella ribs, the main components of which are as follows by weight: C 0.15-0.30%, Si≤0.17%, Mn 0.60-1.20%, P≤0.025%, S≤0.025%, Ti 0.010-0.05%, B 0.0005-0.0040%, and the rest are Fe and unavoidable impurities.

[0008] Preferably, its main components are, by weight percentage, C 0.20%, Si 0.03%, Mn 0.84%, P 0.011%, S 0.006%, Ti 0.034%, B 0.0020%, and the rest are Fe and inevitable trace residual elements and impurities.

[0009] Preferably, its main components are, by weight percentage, C 0.21%, Si 0.05%, Mn 0.84%, P 0.010%, S 0.007%, Ti 0.028%, B 0.0020%, and the rest are Fe and inevitable trace residual elements and impurities.

[0010] The present invention also provides a method for producing a wire rod for a high-ductility umbrella rib, comprising the following steps:

[0011] (1) pre-treating the molten iron for desulfurization to reduce the sulfur content to below 0.020%;

[0012] (2) The desulfurized iron water and scrap steel are smelted in a converter to carry out carbon reduction and dephosphorization operations so that the C and P element contents reach the target requirements, and the steel tapping temperature is controlled to be ≥1610℃.

[0013] (3) LF refining is carried out, calcium aluminate slag system is used, the argon blowing intensity is strictly controlled, the molten steel is prevented from contacting with air, the oxygen content is reduced, and the inclusion control level is improved. The control target of the finished molten steel after refining is: C 0.15-0.30%, Si≤0.17%, Mn 0.60-1.20%, P≤0.025%, S≤0.025%, Ti 0.010-0.05%, B 0.0005-0.0040%, and the rest is Fe and unavoidable impurities;

[0014] (4) The refined molten steel is cast in protective casting, and the continuous casting billet size is 180mm*240mm; the superheat during the casting process is 20-35℃, and the casting speed is 1.05-1.15m / min, which reduces the element segregation and provides a basis for subsequent microstructure control;

[0015] (5) To ensure product quality, after the billet is cooled to room temperature, the billet surface is inspected and slag is removed to ensure that there are no defects on the billet surface that affect the surface quality of the finished product;

[0016] (6) The qualified continuous casting billet is placed in a heating furnace for heating. The temperature in the furnace is 1100-1180°C and the actual temperature of the billet is 1040-1100°C. The air and gas ratio is controlled so that the residual oxygen content in the furnace is ≤1.5% to avoid decarburization on the surface of the billet. The heated billet is rolled into 5.5 mm specification wire by 33 passes of rough rolling, final rolling, pre-finishing rolling, finishing rolling and sizing reduction unit. During the rolling process, the temperature of the rolled piece is maintained at 860-950°C (austenite region) by a high-speed wire online water cooling automatic control system.

[0017] (7) After rolling, the wire rod is formed into a loose coil flat state by a spinning machine, and the whole wire rod is immersed in a liquid salt solution of 350-500°C through a roller, so that the salt bath temperature is lower than the starting temperature of bainite phase transformation. A motor-driven roller is set at the bottom of the salt solution to adjust the roller speed, thereby adjusting the isothermal time of the wire rod in the salt solution. The isothermal salt bath time is 50s-170s to ensure that the austenite completely undergoes bainite phase transformation and obtains a uniform high-plasticity bainite structure. After the phase transformation is completed, the wire rod is transported to the coiling station for collection via a roller.

[0018] Preferably, the actual temperature of the blank in step (6) is 1070-1080°C.

[0019] Preferably, in step (7), the salt bath temperature is 470-780° C., and the isothermal salt bath time is 100-120 s.

[0020] Preferably, in step (6), the starting rolling temperature is 970-975°C, the finishing rolling inlet temperature is 900-915°C, and the sizing inlet temperature is 900°C.

[0021] Compared with the prior art, the advantages and positive effects of the present invention are:

[0022] The present invention refines the grains and improves the plasticity without reducing the strength of the product by optimizing the component design; the temperature is stably controlled during the heating and rolling processes to ensure that the initial organizational state of the wire rod before entering the salt tank is uniform; a constant temperature cooling method of completely immersing the wire rod in a constant temperature salt solution online is adopted to solve the fundamental problems of insufficient cooling rate on the traditional Stelmor line and inconsistent cooling rates in the middle and overlapping positions of the loose coil distribution wire rod, thereby achieving uniform and controllable cooling rate, and at the same time combining the speed adjustment of the roller at the bottom of the salt tank to control the holding time, so that the organization undergoes a complete phase change, avoiding the transformation of the residual austenite into a martensite organization after leaving the line, so that the wire rod obtains a uniform bainite organization with a higher deformation ability.

[0023] The high-plasticity steel wire rod for umbrella ribs produced by the present invention has a surface shrinkage rate that is 15% higher than that of conventional wire rods, and can be directly processed into umbrella rib materials without annealing after cold drawing. Test results show that its cold processing performance is better than that of 35 steel, and the surface finish after cold processing is good, and the surface quality qualification rate is ≥99%. At the same time, due to the rapid cooling process after rolling, the thickness of the third oxidation scale on the surface of the wire rod is 4-6μm, which is lower than 8-15μm produced by 35 steel through the Stelmor process, and the metal yield rate is improved, further reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The microstructure diagram of the wire rod for umbrella ribs prepared in Example 1 of the present invention;

[0025] Figure 2 This is a microstructural diagram of the wire rod for umbrella ribs prepared in Example 2 of the present invention;

[0026] Figure 3 This is a microstructure diagram of the wire rod for umbrella ribs prepared in the comparative example of the present invention; DETAILED DESCRIPTION

[0027] In order to better understand the present invention, a detailed description is given below in conjunction with the accompanying drawings and embodiments.

[0028] Example 1

[0029] A method for producing a wire rod for a high-ductility umbrella rib comprises the following steps:

[0030] (1) Hot metal pretreatment: The hot metal is subjected to desulfurization pretreatment to reduce the sulfur content to below 0.020%;

[0031] (2) Converter smelting: Desulfurized molten iron and scrap steel are smelted in a converter to ensure that the C and P content reaches the target requirements, while controlling the steel tapping temperature to ≥1610°C.

[0032] (3) Refining: LF refining is carried out, calcium aluminate slag system is used, the argon blowing intensity is strictly controlled, the molten steel is prevented from contacting with air, the oxygen content is reduced, and the inclusion control level is improved. The control target of the finished molten steel after refining is: C 0.15-0.30%, Si≤0.17%, Mn0.60-1.20%, P≤0.025%, S≤0.025%, Ti 0.010-0.05%, B0.0005-0.0040%, and the rest is Fe and unavoidable impurities;

[0033] (4) Continuous casting: The refined molten steel is cast in a protective casting process, and the continuous casting billet size is 180mm*240mm; the superheat during the casting process is 20-35℃, and the casting speed is 1.05-1.15m / min;

[0034] (5) Billet finishing: Cool the billet to room temperature, inspect the billet surface and remove slag;

[0035] (6) Heating and rolling: The qualified continuous casting billet is placed in a heating furnace for heating, the temperature in the furnace is 1100-1180°C, the actual billet temperature is 1080°C, and the air and gas ratio is controlled so that the residual oxygen content in the furnace is ≤1.5%; the heated billet is rolled into 5.5mm specification wire rod through rough rolling, final rolling, pre-finishing rolling, finishing rolling and sizing reduction unit, wherein the starting rolling temperature is 975°C, the finishing rolling inlet temperature is 912°C, and the sizing reduction inlet temperature is 900°C. During the rolling process, the temperature of the rolled piece is maintained at 860-950°C through the high-speed wire rod online water cooling automatic control system;

[0036] (7) Wire laying isothermal treatment: After rolling, the wire rod is laid flat on the wire laying machine, and the wire laying temperature is 897°C. The loose coil is immersed in a 475°C liquid salt solution through a roller, and exits the salt tank after 110 seconds to ensure that the austenite undergoes a complete bainite phase transformation. After the phase transformation is completed, the wire rod is transported to the coiling station for collection via a roller.

[0037] The qualified continuous casting steel billet smelted by the above steps has the following components: C: 0.20%, Si: 0.03%, Mn: 0.84%, P: 0.011%, S: 0.006%, Ti: 0.034%, B: 0.0020%, and the rest are Fe and inevitable trace residual elements and impurities.

[0038] The wire rod prepared by the above steps was stored at room temperature for 72 hours and then subjected to structure and performance testing. Figure 1 The microstructure of the sample is shown in the figure. It can be seen from the figure that the wire rod structure is mainly bainite, and the proportion of bainite is ≥98%. The same circle is divided into 8 samples for mechanical property testing. The test results are shown in Table 1. The tensile strength is 689-712MPa, the average tensile strength is 701MPa, and the fluctuation is 23MPa; the cross-sectional shrinkage is 78-83%, the average is 80.1%, and the fluctuation is 5%.

[0039] Table 1 Mechanical properties test results of wire rod in the same circle of Example 1

[0040] Sample No. 1-1 1-2 1-3 1-4 1-5 1-6 1-7 1-8 Tensile strength Rm / MPa 707 692 689 697 712 710 699 699 Sectional shrinkage / % 78 78 83 79 82 79 80 82

[0041] Example 2

[0042] A method for producing a wire rod for a high-ductility umbrella rib comprises the following steps:

[0043] (1) pre-treating the molten iron for desulfurization to reduce the sulfur content to below 0.020%;

[0044] (2) The desulfurized iron water and scrap steel are smelted in a converter to make the C and P element contents reach the target requirements, while the steel tapping temperature is controlled to be ≥1610℃.

[0045] (3) LF refining is carried out, calcium aluminate slag system is used, the argon blowing intensity is strictly controlled, the molten steel is prevented from contacting with air, the oxygen content is reduced, and the inclusion control level is improved. The control target of the finished molten steel after refining is: C 0.15-0.30%, Si≤0.17%, Mn 0.60-1.20%, P≤0.025%, S≤0.025%, Ti 0.010-0.05%, B 0.0005-0.0040%, and the rest is Fe and unavoidable impurities;

[0046] (4) The refined molten steel is cast in protective casting, and the continuous casting billet size is 180mm*240mm; the superheat during the casting process is 20-35℃, and the casting speed is 1.05-1.15m / min;

[0047] (5) Cooling the blank to room temperature, inspecting the surface of the blank and removing slag;

[0048] (6) The qualified continuous casting billet is placed in a heating furnace for heating, the temperature in the furnace is 1100-1180°C, the actual billet temperature is 1075°C, and the air and gas ratio is controlled so that the residual oxygen content in the furnace is ≤1.5%; the heated billet is rolled into 5.5mm specification wire rod through rough rolling, final rolling, pre-finishing rolling, finishing rolling and sizing reduction unit, wherein the starting rolling temperature is 971°C, the finishing rolling inlet temperature is 901°C, and the sizing reduction inlet temperature is 900°C. During the rolling process, the temperature of the rolled piece is maintained at 860-950°C through a high-speed wire rod online water cooling automatic control system;

[0049] (7) After rolling, the wire rod is laid flat on a spinning machine at a spinning temperature of 910°C. The entire loose coil is immersed in a 480°C liquid salt solution via a roller and exits the salt tank after 110 seconds to ensure that the austenite undergoes a complete bainite phase transformation. After the phase transformation is completed, the wire rod is transported to the coiling station via a roller.

[0050] The qualified continuous casting steel billet smelted by the above steps has the following components: C: 0.21%, Si: 0.05%, Mn: 0.84%, P: 0.010%, S: 0.007%, Ti: 0.028%, B: 0.0020%, and the rest are Fe and inevitable trace residual elements and impurities.

[0051] The wire rod prepared by the above steps was stored at room temperature for 72 hours and then subjected to structure and performance testing. Figure 2The microstructure of the sample is shown in the figure, from which it can be seen that the wire rod structure is mainly bainite. The same circle is divided into 8 samples for mechanical property testing. The test results are shown in Table 2. The tensile strength is 678-700MPa, the average tensile strength is 690MPa, and the fluctuation is 22MPa; the cross-sectional shrinkage is 77-80%, the average is 78.4%, and the fluctuation is 3%.

[0052] Table 2 Mechanical properties test results of wire rod in the same circle of Example 2

[0053] Sample No. 2-1 2-2 2-3 2-4 2-5 2-6 2-7 2-8 Tensile strength Rm / MPa 694 689 689 688 678 693 689 700 Sectional shrinkage / % 79 78 77 79 80 79 77 78

[0054] Comparative Example:

[0055] In the prior art, 35 steel is used for the umbrella ribs, and its components are C: 0.32%, Si: 0.25%, Mn: 0.65%, P: 0.015%, S: 0.016% in weight percentage, and the rest are Fe and inevitable trace residual elements and impurities.

[0056] The above-mentioned umbrella ribs are made of 35 steel by the following steps:

[0057] (1) pre-treating the molten iron for desulfurization to reduce the sulfur content to below 0.020%;

[0058] (2) The desulfurized iron water and scrap steel are smelted in a converter to make the C and P element contents reach the target requirements, while the steel tapping temperature is controlled to be ≥1610℃.

[0059] (3) Carry out LF refining, use calcium silicate slag system, strictly control the argon blowing intensity, avoid contact between molten steel and air, reduce oxygen content, and improve inclusion control level;

[0060] (4) The refined molten steel is cast in protective casting, and the continuous casting billet size is 180mm*240mm; the superheat during the casting process is 20-35℃, and the casting speed is 1.05-1.15m / min;

[0061] (5) Cooling the blank to room temperature, inspecting the surface of the blank and removing slag;

[0062] (6) The qualified continuous casting billet is placed in a heating furnace for heating, and the actual billet temperature is 1040°C; the heated billet is rolled into 5.5 mm specification wire rod by rough rolling, final rolling, pre-finishing rolling, finishing rolling and sizing reduction unit, wherein the starting rolling temperature is 934°C, the finishing rolling inlet temperature is 902°C, and the sizing reduction inlet temperature is 890°C.

[0063] (7) After rolling, the wire rod is formed into loose coils by a spinning machine with a spinning temperature of 909°C. It is then cooled by a Stelmor wire fan at a rate of 11-17°C / s to 580-670°C.

[0064] like Figure 3 The microstructure of the 35 steel for umbrella ribs produced by the above steps is shown in the figure. It can be seen from the figure that the wire rod structure is mainly ferrite + pearlite. The same circle is divided into 8 samples for mechanical property testing. The test results are shown in Table 3. The tensile strength is 645-656MPa, the average is 649MPa, and the fluctuation is 21MPa; the cross-sectional shrinkage is 60-67%, the average is 63.8%, and the fluctuation is 7%. It can be seen that its tensile strength is lower than that of the high-ductility umbrella rib wire rod produced in Examples 1 and 2, and its cross-sectional shrinkage is less than that of the high-ductility umbrella rib wire rod produced in Examples 1 and 2.

[0065] Table 3 Mechanical properties test results of comparative wire rod with the same circle

[0066] Sample No. 3-1 3-2 3-3 3-4 3-5 3-6 3-7 3-8 Tensile strength Rm / MPa 645 649 648 651 656 647 651 646 Sectional shrinkage / % 64 67 64 64 63 60 64 65

[0067] The high-ductility wire rod for umbrella ribs and the 35 steel wire rod for umbrella ribs produced in Example 1 are both processed by an annealing-free processing technology, and the specific steps are: 5.5mm wire rod → pickling → continuous drawing to 2.75mm → direct rolling into thin flat wire (0.35-0.26mm*6.0mm, U-shaped umbrella rib material) without annealing. The high-ductility wire rod for umbrella ribs produced in Example 1 was not found to be broken by drawing or cracked after flattening during this process. The mechanical properties of the 2.75mm semi-finished fine wire of Example 1 and the comparative example were further tested. The test results are shown in Table 4. It can be seen from the table that the 2.75mm steel wire processed from the wire rod prepared in Example 1 has a cross-sectional shrinkage rate of 67.8-72%, good plasticity, and significantly improved shaping compared with traditional 35 steel.

[0068] Table 4 Mechanical properties test results of 2.75 mm fine wire made of wire rods in Example 1 and Comparative Example

[0069]

[0070] The 2.75 mm steel wire processed from the wire rod prepared in Example 1 is further directly rolled into flat wire materials with different thicknesses of 0.35-0.26 mm without annealing, and then bent into U-shaped umbrella ribs. It can be found that no cracks were found in the full inspection of the flat wire and the finished product. Its cold working performance is better than that of 35 steel. The surface finish after cold working is good, and the surface quality pass rate is ≥99%, which meets the product requirements.

[0071] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A wire rod for umbrella ribs with high ductility, characterized in that: Its main components are as follows by weight percentage: C 0.15-0.30%, Si≤0.17%, Mn 0.60-1.20%, P≤0.025%, S≤0.025%, Ti 0.010-0.05%, B0.0005-0.0040%, and the rest are Fe and unavoidable impurities.

2. The wire rod for high ductility umbrella ribs according to claim 1, characterized in that: Its main components are as follows by weight percentage: C 0.20%, Si 0.03%, Mn 0.84%, P 0.011%, S 0.006%, Ti 0.034%, B 0.0020%, and the rest are Fe and inevitable trace residual elements and impurities.

3. The wire rod for high ductility umbrella ribs according to claim 1, characterized in that: Its main components are as follows by weight percentage: C 0.21%, Si 0.05%, Mn 0.84%, P 0.010%, S 0.007%, Ti 0.028%, B 0.0020%, and the rest are Fe and inevitable trace residual elements and impurities.

4. A method for producing a wire rod for a high-ductility umbrella rib, characterized in that: The following steps are involved: (1) pre-treating the molten iron for desulfurization to reduce the sulfur content to below 0.020%; (2) The desulfurized iron water and scrap steel are smelted in a converter to make the C and P element contents reach the target requirements, while the steel tapping temperature is controlled to be ≥1610℃. (3) LF refining is carried out, calcium aluminate slag system is used, the argon blowing intensity is strictly controlled, the molten steel is prevented from contacting with air, the oxygen content is reduced, and the inclusion control level is improved. The control target of the finished molten steel after refining is: C 0.15-0.30%, Si≤0.17%, Mn 0.60-1.20%, P≤0.025%, S≤0.025%, Ti 0.010-0.05%, B 0.0005-0.0040%, and the rest is Fe and unavoidable impurities; (4) The refined molten steel is cast in protective casting, and the continuous casting billet size is 180mm*240mm; the superheat during the casting process is 20-35℃, and the casting speed is 1.05-1.15m / min; (5) Cooling the blank to room temperature, inspecting the surface of the blank and removing slag; (6) placing the qualified continuous casting billet into a heating furnace for heating, wherein the temperature in the furnace is 1100-1180° C., the actual temperature of the billet is 1040-1100° C., and the ratio of air to gas is controlled so that the residual oxygen content in the furnace is ≤1.5%; the heated billet is rolled into 5.5 mm specification wire by rough rolling, final rolling, pre-finishing rolling, finishing rolling and sizing reduction unit, and during the rolling process, the temperature of the rolled piece is maintained at 860-950° C. by a high-speed wire online water cooling automatic control system; (7) After rolling, the wire rod is formed into a loose coil and laid flat by a spinning machine. The whole wire rod is immersed in a liquid salt solution at 350-500°C via a roller. The isothermal salt bath time is 50-170s to ensure that the austenite undergoes a complete bainite phase transformation. After the phase transformation is completed, the wire rod is transported to the coiling station for collection via a roller.

5. The method for producing a wire rod for a high-ductility umbrella rib according to claim 1, characterized in that: In step (6), the actual temperature of the blank is 1070-1080°C.

6. The method for producing a wire rod for a high-ductility umbrella rib according to claim 1, characterized in that: In step (7), the salt bath temperature is 470-480° C., and the isothermal salt bath time is 100-120 s.

7. The method for producing a wire rod for a high-ductility umbrella rib according to claim 1, characterized in that: In step (6), the starting rolling temperature is 970-975°C, the finishing rolling inlet temperature is 900-915°C, and the sizing inlet temperature is 900°C.